Effects of processing conditions on properties and morphology of chitosan/lovastatin particles. Issue 1 (25th February 2019) - Thang, Dam Xuan; Chinh, Nguyen Thuy; Ngoc, Dinh Hong; Tung, Nguyen Quang; Hoang, Thai
Abstract: This paper presents the effect of processing conditions on properties and morphology of chitosan particles loading lovastatin as a model drug. The processing conditions were investigated here including solvents for dissolution of drug, emulsifier content and temperature of drying process. Two solvents chosen to dissolve lovastatin were ethanol and dichloromethane. Polyethylene oxide used as an emulsifier with different contents for preparation of chitosan/lovastatin particles. Two methods for evaporation of water in the samples were freeze‐drying and natural air drying in convection oven. The characteristic properties and morphology of chitosan/lovastatin particles were observed, determined and evaluated by Fourier transform infrared spectra, size distribution, and scanning emission microscopy images. From the above data and images, we can find the most suitable condition for the preparation of chitosan/lovastatin particles.